Developing a Loop-Mediated Isothermal Amplification Assay for the Rapid Detection of Seven Respiratory Viruses including SARS-CoV-2 - Min-Young Lee; Vu-Minh Phan; Woo-In Lee; Yee-Hyung Kim; Sung-Wook Kang; Tae-Seok Seo (Medicina, 2022)
Background and Objectives: The coronavirus disease (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), continues to be a pandemic even in 2022. As the initial symptoms of COVID-19 overlap with those of infections from other respiratory viruses, an accurate and rapid diagnosis of COVID-19 is essential for administering appropriate treatment to patients. Currently, the most widely used method for detecting respiratory viruses is based on real-time polymerase chain reaction (PCR) and includes reverse-transcription real-time quantitative PCR (RT-qPCR). However, RT-qPCR assays require sophisticated facilities and are time-consuming. This study aimed to develop a real-time quantitative loop-mediated isothermal amplification (RT-qLAMP) assay and compare its analytical performance with RT-qPCR. Materials and Methods: A total of 315 nasopharyngeal swabs from patients with symptoms of respiratory infections were included in this study. A primary screening of the specimens was performed using RT-qPCR. RNA/DNA from standard strains for respiratory viruses and heat-inactivated preparations of standard strains for SARS-CoV-2 were used to evaluate the accuracy and target specificity of the RT-qLAMP assay. Results: We successfully developed an RT-qLAMP assay for seven respiratory viruses: respiratory syncytial virus (RSV) A, RSV B, adenovirus, influenza (Flu) A (H1N1 and H3N2), Flu B, and SARS-CoV-2. RT-qLAMP was performed in a final reaction volume of 9.6 µL. No cross-reactivity was observed. Compared with the RT-PCR results, the sensitivity and specificity of the RT-qLAMP assay were 95.1% and 100%, respectively. The agreement between the two methods was 97.1%. The median amplification time to RT-qLAMP positivity was 22:34 min (range: 6:80–47:98 min). Conclusions: The RT-qLAMP assay requires a small number of reagents and samples and is performed with an isothermal reaction. This study established a fast, simple, and sensitive test that can be applied to point-of-care testing devices to facilitate the detection of respiratory viruses, including SARS-CoV-2.